2023
DOI: 10.1111/acel.13960
|View full text |Cite
|
Sign up to set email alerts
|

Associations between cardiorespiratory fitness and lifestyle‐related factors with DNA methylation‐based ageing clocks in older men: WASEDA'S Health Study

Abstract: DNA methylation‐based age estimators (DNAm ageing clocks) are currently one of the most promising biomarkers for predicting biological age. However, the relationships between cardiorespiratory fitness (CRF), measured directly by expiratory gas analysis, and DNAm ageing clocks are largely unknown. We investigated the relationships between CRF and the age‐adjusted value from the residuals of the regression of DNAm ageing clock to chronological age (DNAmAgeAcceleration: DNAmAgeAccel) and attempted to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 101 publications
4
15
0
Order By: Relevance
“…Our previous study also found a significant negative relationship between CRF and age acceleration, but this study included only men 9 . Most other previous studies have examined the relationship between physical activity and age acceleration in the same cohort of men and women (adjusted for sex) through cross-sectional designs 9 . Considering the overall findings of previous studies that suggest that exercise may delay epigenetic age progression, the relationship between exercise and multi-organ epigenetic age is worth investigating, along with the development of a rat clock that can capture biological aging with high precision across multiple organs, as well as their sex differences.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Our previous study also found a significant negative relationship between CRF and age acceleration, but this study included only men 9 . Most other previous studies have examined the relationship between physical activity and age acceleration in the same cohort of men and women (adjusted for sex) through cross-sectional designs 9 . Considering the overall findings of previous studies that suggest that exercise may delay epigenetic age progression, the relationship between exercise and multi-organ epigenetic age is worth investigating, along with the development of a rat clock that can capture biological aging with high precision across multiple organs, as well as their sex differences.…”
Section: Discussionmentioning
confidence: 79%
“…Cross-sectional studies in human populations have shown that physical activity and CRF are associated with delayed epigenetic age progression [7][8][9][10] . In mice, late-life exercise training may delay skeletal muscle epigenetic aging via skeletal muscle-specific epigenetic clock(s) 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…The link between CRF and DNA methylation clocks is also an emerging area of research, bridging physical fitness with molecular biomarkers that measure the rate or pace of aging. Kawamura et al (2023) describe associations between CRF and lifestyle-related factors with DNA methylation in a cohort of older men, finding that higher CRF levels correlated with delayed biological aging, though lifestyle factors (e.g., smoking) had a more significant impact, highlighting the nuanced interplay between fitness, behavioral exposures, and biological aging.…”
Section: B I Olog I C Alpathwaysmentioning
confidence: 94%
“…The procedure from blood collection to sample storage has been described previously (15, 31). The participants were instructed to fast for at least 12 h the night before blood collection.…”
Section: Methodsmentioning
confidence: 99%
“…Accumulating evidence suggests that the epigenetic clock is associated with lifestyle factors, such as body composition (11), physical activity (12,13) and physical fitness levels (14,15), smoking (16), and alcohol intake (16), and can be delayed or reversed by pharmacological and lifestyle interventions (17)(18)(19)(20). It has also been suggested that healthy dietary patterns, diets rich in fruits and vegetables, and mediterranean diets may delay the epigenetic clocks (21)(22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%